Els bandos de Valènsia o la paraula de sen Vicent Ferrer (1855): el primer milacre de Vicent Boix. - FUERTES ZAPATA, JUAN VICENTE (Scripta, 2020)
One of the first authors of milacres with name and surname known, was the historian of Valencia, Vicent Boix i Ricarte (1813-1880). That activity was sporadic, but it is very possible that its beginning can be placed on 1855, date of the fourth centenary of the canonization of St. Vicente Ferrer. In that celebration, in addition, Boix was the one in charge to elaborate the commemorative book and of that year it is the publication of Els bandos de Valènsia o la paraula de sen Vicent Ferrer, that analyzes in this article.